2008
DOI: 10.1080/14649350802481488
|View full text |Cite
|
Sign up to set email alerts
|

Network Governance in Contested Urban Landscapes

Abstract: Urban planning is one of the policy fields where new forms of governance are developing. The article focuses on governance networks as one emergent form of governance in urban planning. In governance literature, discourse networks are seen as a threat to representative democracy. This article argues that the consequences for democracy depend on the type of network that develops and its performance in relation to democratic norms. Governance networks are discussed through the lens of democratic network governan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
(7 reference statements)
3
26
0
Order By: Relevance
“…• Fourthly, it has been shown that without connections to formal institutions, it is hard for governance networks to make a change [17,25]. The planning authority as metagovernor provides such a connection.…”
Section: Bmentioning
confidence: 99%
See 4 more Smart Citations
“…• Fourthly, it has been shown that without connections to formal institutions, it is hard for governance networks to make a change [17,25]. The planning authority as metagovernor provides such a connection.…”
Section: Bmentioning
confidence: 99%
“…The result was leadership by a highly competent network, capable of constructing alternative perspectives and visions on city planning". [17].…”
Section: Bmentioning
confidence: 99%
See 3 more Smart Citations